Х`2+2х-4/(х'2-16)*2х+9х/(4-х)(х+4) с объяснением

rustam05mirzaev rustam05mirzaev    1   27.06.2019 10:30    0

Ответы
hrapatiynickita hrapatiynickita  21.07.2020 20:53
\frac{x^2+4x-4}{x^2-16}*2x+ \frac{9x}{(4-x)(x+4)}=\\\\
 \frac{2x^3+4x^2-8x}{(x-4)(x+4)}+ \frac{9x}{(4-x)(x+4)}=\\\\
 \frac{8x^3+16x^2-32x-2x^4-4x^3+8x^2+9x^2-36x}{(x-4)(x+4)(4-x)}=\\\\
 \frac{-2x^4+4x^3+33x^2-68x}{(x-4)(x+4)(4-x)}= \frac{x(4-x)(2x^2+4x-17)}{(x-4)(x+4)(4-x)}=\\\\
 \frac{x(2x^2+4x-17)}{(x-4)(x+4)}= \frac{2x^3+4x^2-17x}{x^2-16}

Возможно, существует более оптимальная версия решения
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра